VARIABILITY OF MITOCHONDRIAL CYTOCHROME OXYDASE SUBUNIT I GENE SEQUENCE IN SPECIES OF THE GENERA AEDES AND OCHLEROTATUS (DIPTERA: CULICIDAE) - N. V. Khrabrova; Yu. V. Andreeva; O. V. Vaulin; S. S. Alekseeva; A. K. Sibataev (Вавиловский журнал генетики и селекции)
Sequence variation in the 538-bp fragment from the 5′ end of the COI region was analyzed to test its usefulness in the identification of 15 mosquito species of the genera Aedes and Ochlerotatus (Diptera: Culicidae) from Tomsk and Kemerovo regions and 14 species from GenBank. The divergences between congeneric species averaged 7,8 % (from 0,7 to 13,1 %), whereas those for conspecific individuals averaged 0,57 % (0 to 1,6 %). The sequences for four species pairs (3,7 %) showed < 2 % divergence. In most cases, individuals of a single species grouped closely together, but deeper divergences were detected in two species (Och. euedes and Ae. vexans).